Stabilization of Highway Pavement Base Using Coal Ash, Experience of Georgia: Laboratory Characterization and Field Evaluation - Aleks Burduladze; Tengiz Papushvili; Nugzar Rurua; Beqa Khetsuriani; Valentin Romanovski (Engineering Reports)
ABSTRACT The development of the road network is a topical issue for any country. One of the promising areas in this area is the use of waste for the purpose of its disposal, as well as obtaining road surfaces of better quality. This approach allows not only to reduce the negative impact on the environment but also to reduce the cost of road surface production and to improve the transport and operational characteristics of the road surface. The article discusses the studies of secondary material slag ash from fuel combustion as a replacement for bitumen. The optimal ash additive was 12 wt%. When using ash to stabilize the base of the road surface, the dynamic deformation characteristic increases by 104%, and under static load, the deformation modulus by 51% and the elastic modulus by 89%. The performance of the coal ash‐stabilized mixtures was superior to traditional materials such as bitumen‐cement mixtures across multiple metrics. In terms of compressive strength, the coal ash mixture (12% ash, 4% cement) demonstrated a 20% improvement compared to the bitumen‐cement mixture. Similarly, its tensile strength was 18% higher due to the pozzolanic properties of coal ash, which enhanced bonding. The California bearing ratio (CBR) for the ash mixture was 127%, outperforming the bitumen‐cement mixture (118%) and untreated sand‐gravel mixture (71%). Under dynamic loading, the deformation modulus of the ash‐based mixture (125.43 MPa) was 1.2 times higher than the bitumen‐cement mixture (106.02 MPa) and more than double that of the untreated mixture (61.38 MPa). These results demonstrate that coal ash significantly improves the mechanical properties and durability of road base layers, providing a compelling case for its use over traditional materials.